Historiografi Hadis: Analis Embrio, Pemetaan dan Perkembangannya - Ja'far Assagaf (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2022)
This article examines the historiography of hadith from the beginning of its emergence, then it becomes a separate form in the study of Islamic history. This study uses a descriptive qualitative approach with a content analysis method to find three parts of hadith historiography, namely: embryo, mapping, and development. This study concludes that the embryo of the historiographical emergence of hadith is a historical reality that was real at the time it was reported, and the historical reality of the existence of written works in the second-century hijrah. Both are sources that are interrelated and cannot be separated. At the source mapping level, hadith historiography obtains biographical information on rijal al-hadith from the books al-Sirah, al-Tarikh, al-Thabaqah, and al-Manaqib even though these books are also sources of Islamic historiography. Another further finding is that the development of modern hadith historiography is more on the historical trajectory of hadith with several forms that still revolve around classical hadith issues. Social, political, and other approaches can function as integration in hadith historiography so that they can examine the development of hadith in modern society. Abstrak: Artikel ini mengkaji historiografi hadis dari awal kemunculannya sebagai embrio, kemudian menjadi bentuk tersendiri dari jenis kitab dalam kajian sejarah Islam. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode analisis isi untuk menemukan tiga bagian historiografi hadis yakni: embrio, pemetaan, dan pengembangan. Kajian ini menemukan bahwa embrio kemunculan historiografis hadis adalah realitas sejarah yang nyata pada saat diberitakan, dan realitas sejarah keberadaan karya tulis pada abad kedua hijriyah. Keduanya merupakan sumber yang saling berkaitan dan tidak dapat dipisahkan. Pada pemetaan sumber, historiografi hadis memperoleh informasi biografi rijal al-hadits dari kitab-kitab al-Sirah, al-Tarikh, al-Thabaqah, dan al-Manaqib meskipun kitab-kitab tersebut juga merupakan sumber historiografi Islam. Temuan lain selanjutnya adalah perkembangan historiografi hadis modern lebih pada lintasan sejarah hadis dengan beberapa bentuk yang masih berkisar pada persoalan hadis klasik. Pendekatan sosial, politik dan lainnya dapat berfungsi sebagai integrasi dalam historiografi hadis yang mampu mengkaji perkembangan hadis dalam masyarakat modern, media sosial, dan lain-lain.